The Influence Of CSR And Political Connections On Company Performance By Moderating Governance Mechanisms - Saraswati, Wiwik; Makherta, Ika; Nurlia, Nurlia (Perspektif Akuntansi, 2025)
This study aims to determine and analyze the influence of sustainability reporting practices and the quality of CSR disclosures as well as political connections to company performance, either directly or indirectly, by involving governance mechanisms as mediators. This study uses secondary data on banking companies listed on the Indonesia Stock Exchange from 2013 to 2021. The sample selection method uses a purposive sampling method with several criteria to produce 383 observations. The analysis technique used is simple and multiple linear regression analysis using STATA 12 application and Sobel test for mediation test. The results of this study provide empirical evidence that the practice of reporting on the sustainability of banking companies cannot improve the company's performance, this is because banks have not fully prepared sustainability reports and used insurance services, while the quality of CSR disclosure and political connections can improve company performance. The results also show that the practice of sustainability reporting and the quality of CSR disclosure as well as political connections can improve company performance through governance mechanisms.